Dynamic security corrective control by UPFCs. - Bruno, S. (IEEE Transactions on power systems)
This paper deals with the development of a nonlinear programming methodology for evaluating corrective actions to improve the dynamic security of power systems when transient instability is detected. Remedial actions are implemented by exploiting the fast response of unified power flow controllers (UPFCs). The algorithm is implemented and tested on the Italian grid